Socioeconomic inequalities, modifiable lifestyle risk factors, and retinal vessel calibers: The African‐PREDICT Study. (8th June 2021) - Maugana, Vuledzani Felicia; Kruger, Ruan; Schutte, Aletta Elisabeth; Smith, Wayne
Abstract: Objective: Lifestyle risk factors vary between socioeconomic status (SES) groups and may influence cardiovascular function differently. The retinal microvasculature allows for monitoring early changes in cardiovascular health, and therefore, we investigated whether retinal vessel calibers associate differently with modifiable risk factors in different SES groups. Methods: We included 1064 young adults (aged 20–30 years) grouped by low and high SES. The central retinal artery and vein equivalents (CRAE, CRVE) were determined from fundus images captured using the Dynamic Retinal Vessel Analyzer (Imedos Systems GmbH, Jena, Germany). We collected anthropometry, self‐reported alcohol consumption, and biochemical data. Results: Retinal vessel calibers did not differ between SES groups ( p ≥ .80) after adjusting for sex and ethnicity. Unique independent associations were observed in the low SES group, where CRAE ( β = 0.08, p = .042) and CRVE ( β = .14, p = .001) associated positively with cotinine and body mass index, respectively. In the high SES group, CRAE ( β = –0.09, p = .027) associated negatively with alcohol consumption. Conclusion: At young ages, retinal vessel calibers associated differently with modifiable lifestyle risk factors within each SES group. Our data highlight the importance of detecting adverse lifestyle risk factors among young adults from diverse socioeconomic settings to improve prevention of cardiovascular disease.